PENGARUH EKSTRAK DAUN KENIKIR (Tagetes erecta L.) SEBAGAI REPELLENT TEHADAP NYAMUK Aedes spp. - Dwisyahputra Hutagalung; Irnawati Marsaulina; Evi Naria (Lingkungan dan Kesehatan Kerja, 2013)
Effect of extract marigolds (Tagetes erecta L.) leaves as the repellent to Aedes spp mosquitoes. Recently, in Indonesia Dengue Hemorrhagic Fever (DHF) is still public health problems. The morbidity rate for this desease tends to raise for the period of 2005-2009. This desease is an contagious desease caused by the dengue virus and transmitted through the Aedes aegypti, Aedes albopictus mosquitoes.The aim of this research was to analyze the effect of extract marigolds (Tagetes erecta L.) leaves as the repellent to the Aedes spp.The design of this research was the quasi-experimental with Completely Randomized Design (CRD) in which the experiments were conducted by using six variation of concentration of the extract which are 0% (as a control), 1%, 2%, 3%, 4%, 5% in three replication.The result of the study showed that there was an effect of the extract of marigolds (Tagetes erecta L.) leaves as the repellent to Aedes spp. The calculation of average protection power of extrack marigold (Tagetes erecta L.) leaves on concentration 1% was 37,5%, on concentration 2% was 62,5%, on concentration 3% was 75%, on concentration 4% was 87,5%, on concentration 5% was 100%.The conclusion was that the level of concentration of marigolds  (Tagetes erecta L.) leaves as the repellent used was 5% because the protection power of this level reached 100%. The outcome from this study is hoped the extract of marigolds (Tagetes erecta L.) leaves can be useful as one of the controller alternatives upon the vector especially for the mosquito and it is also used as the natural insecticide which is safe for both environment and human. Keywords: Aedes spp, marigolds (Tagetes erecta L)